Proposals for equity and improvement of teaching in university virtual classrooms - Alba García Barrera; Ana María de las Heras Cuenca (Centro de Estudios Financieros, 2017)
The present study arises from the need to attend to diversity in distance higher education, where, in recent years, a clear increase of students has been detected, increasing in turn, the teacher-student ratio. This hampers the correct development of the teaching-learning process, which takes place in virtual classrooms with increasingly large groups and with very different characteristics and needs. Based on this complex reality, the authors of the paper reflect on the actions that are currently taking place in distance education and the possible academic and personal consequences that may arise from them. From this analysis they proceed to identify the demands that the university faculty has to attend in the virtual classrooms to respond to the educational and personal needs of each student, guaranteeing the success in their learning. Finally, and in order to help teachers in this work, they offer a series of methodological and didactic proposals that take advantage of the possibilities offered by information and communication technologies (ICT) to bring together people of different provenance and with different training profiles, enriching their learning experience and covering their personal educational needs.